The difficulties of educational psychologist in advising educational institutions - Asesoría Psicosocial, Equipo (Revista de Psicología, 2006)
The following article reviews the experience of a psycho-social assessorship made by the University of Chile. It was framed within the implementation of policies for the Program "Liceo para Todos" of MINEDUC to support the more vulnerable establishments of Middle Education of the country during the periods comprised from 2001-2005. The discussion is centered around the political, theoretical and technical elements directly affecting the work of the educational psychologist in focalized schools.